OWAS inter-rater reliability - Lins, Christian; Fudickar, Sebastian; Hein, Andreas (Applied Ergonomics, 2021)
The Ovako Working posture Assessment System (OWAS) is a commonly used observational assessment method for determining the risk of work-related musculoskeletal disorders. OWAS claims to be suitable in the application for untrained persons but there is not enough evidence for this assumption. In this paper, inter-rater (inter-observer) reliability (agreement) is examined down to the level of individual postures and categories. For this purpose, the postures of 20 volunteers have been observed by 3 varying human raters in a laboratory setting and the inter-rater agreement against reference values was determined. A high agreement of over 98% (κ=0.98) was found for the postures of the arms but lower agreements were found for posture classification of the legs (66−97%,κ=0.85) and the upper body (80−96%,κ=0.85). No significant difference was found between raters with and without intense prior training in physical therapy. Consequently, the results confirm the general reliability of the OWAS method especially for raters with non-specialized background but suggests weaknesses in the reliable detection of a few particular postures.
Keywords: OWAS; Reliability analysis; Risk assessment; Working postures